RGS3 acts as a tumor promoter by facilitating the regulation of the TGF-β signaling pathway and promoting EMT in ovarian cancer - Zizhao Wang; Huating Sun; Shunpeng Zhu; Fang Wang; Quan Li; Jinhua Zhou (Cell Death Discovery)
Abstract Ovarian cancer (OC) is one of the most common and lethal solid malignancies among women, with its incidence steadily rising. Despite substantial advancements in OC research, its pathogenesis remains largely elusive. Recent studies indicate that the regulator of G protein signaling 3 (RGS3) is implicated in tumorigenesis, however, its specific role in OC development has not been extensively investigated. Herein, this research elucidated that the overexpression of RGS3 in OC correlates with adverse clinical pathological features and tumor progression. Furthermore, we demonstrated that silencing RGS3 promotes apoptosis, effectively inhibiting tumor growth and metastasis. Additionally, our findings reveal that RGS3 enhances oncogenic activity by participating in the regulation of the transforming growth factor-beta (TGF-β) pathway and corresponding epithelial-mesenchymal transition (EMT). The in-depth mechanism lies in the RGS3 facilitating the phosphorylation of SMAD2/3 by directly interacting with AT-rich interactive domain-containing protein 3B (ARID3B), which ultimately drives OC cell proliferation and metastasis. Therefore, our results position RGS3 as a significant prognostic biomarker and tumor-promoting factor in OC, underscoring the pivotal role of the RGS3/TGF-β/EMT signaling pathway in the pathogenesis of this malignancy.